Protection of Environment in Industrial Zones and Clusters: A Legal Issues - Diep , Nguyen Trong; Hien , Dinh Tran Ngoc; Nuong , Le Ngoc (Novel Perspectives of Geography, Environment and Earth Sciences Vol. 9, 2023)
The purpose of this study is to present environment protection in industrial clusters and relevant legal issues. In Article 3, Law on Environmental protection 2020 pointed Environmental protection activities mean activities to prevent and limit adverse impacts on the environment; responding to environmental incidents; overcome pollution, environmental degradation, improve environmental quality; rational use of natural resources, biodiversity and response to climate change. This paper also presents some cases of environmental pollutions, via which authorities resolutely organize the implementation of measures to handle violations of the law on environmental protection. It would suggest that Relevant ministries and branches need to review and amend a number of relevant laws, such as the Law on Sanctions of Administrative Violations, the Law on Inspection, the Law on Water Resources, the Law on Science and Technology, etc.